2018
DOI: 10.1088/1748-0221/13/09/p09016
|View full text |Cite
|
Sign up to set email alerts
|

Development of broad-band high-reflectivity multilayer film for positron emission tomography system

Abstract: The use of non-ideal reflective materials and low-precision manual manufacturing technologies is a fundamental technical obstacle blocking the positron emission tomography (PET) systems from achieving better performances. We propose to address that long-standing obstacle with advanced multilayer dielectric coating technologies. We designed an broad-band multilayer high-reflectivity (HR) film that can be coated directly on the surface of ultra-precision polished lutetium-yttrium oxyorthosilicate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…The high-performance reflectors with light-sharing windows can be "printed" on a scintillator directly with high precision, instead of manually gluing reflective materials on the scintillator. 44 A limit of the four-crystals-to-one-SiPM coupling technology developed in this study is that the four C-type crystals on the corners have no DOI capability, as shown in Figs. 1(c In this study, we adapted the method of homogeneous radiation to establish the transfer functions to convert the measured spot shifts into the DOI measurements.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The high-performance reflectors with light-sharing windows can be "printed" on a scintillator directly with high precision, instead of manually gluing reflective materials on the scintillator. 44 A limit of the four-crystals-to-one-SiPM coupling technology developed in this study is that the four C-type crystals on the corners have no DOI capability, as shown in Figs. 1(c In this study, we adapted the method of homogeneous radiation to establish the transfer functions to convert the measured spot shifts into the DOI measurements.…”
Section: Discussionmentioning
confidence: 98%
“…The advanced multilayer dielectric coating technologies is a promising solution to that issue. The high‐performance reflectors with light‐sharing windows can be “printed” on a scintillator directly with high precision, instead of manually gluing reflective materials on the scintillator …”
Section: Discussionmentioning
confidence: 99%
“…There have been studies on various coating methods for scintillators to make the most of the emitted scintillation photons. However, most methods, such as distributed Bragg reflectors, metal coating, modified photonic crystal structures, and a high reflective film method, require special processing for scintillators, causing increased costs for implementation (Xu et al 2018, Gramuglia et al 2021. Furthermore, these methods have mostly focused on maximizing scintillation light collection without considering Cerenkov photons.…”
Section: Additional Discussionmentioning
confidence: 99%
“…4.1(b). Various photonic structures have been reported with ODB's [40,41,42] defined as those spectral regions for which > 90% for all angles. Here we we adopt the same criterium.…”
Section: Chirped-type Bragg Mirrorsmentioning
confidence: 99%